Baseball - Porter, David L., 1941- (Biographical dictionary of American sports. ;, 2000)
Completely revised and expanded, this 4-volume work profiles over 1,450 baseball luminaries and includes 477 new entries. This standard source of first referral provides more biographical information than any other baseball reference available.